Role of ADAM10 and ADAM17 in the Regulation of Keratinocyte Adhesion in Pemphigus Vulgaris - Kugelmann, Daniela; Anders, Maresa; Sigmund, Anna M.; Egu, Desalegn T.; Eichkorn, Ramona A.; Yazdi, Amir S.; Sárdy, Miklós; Hertl, Michael; Didona, Dario; Hashimoto, Takashi; Waschke, Jens (Frontiers in Immunology, 2022)
The severe autoimmune blistering disease Pemphigus vulgaris (PV) is mainly caused by autoantibodies (IgG) against desmoglein (Dsg) 3 and Dsg 1. The mechanisms leading to the development of blisters are not fully understood, but intracellular signaling seems to play an important role. Sheddases ADAM10 and ADAM17 are involved in the turnover of the desmosomal cadherin Dsg2 and ADAM10 has been shown to contribute to acantholysis in a murine pemphigus model. In the present study, we further examined the role of ADAM10 and ADAM17 both in keratinocyte adhesion and in the pathogenesis of PV. First, we found that inhibition of ADAM10 enhanced adhesion of primary human keratinocytes but not of immortalized keratinocytes. In dissociation assays, inhibition of ADAM10 shifted keratinocyte adhesion towards a hyeradhesive state. However, ADAM inhibition did neither modulate protein levels of Dsg1 and Dsg3 nor activation of EGFR at Y1068 and Y845. In primary human keratinocytes, inhibition of ADAM10, but not ADAM17, reduced loss of cell adhesion and fragmentation of Dsg1 and Dsg3 immunostaining in response to a PV1-IgG from a mucocutaneous PV patient. Similarly, inhibition of ADAM10 in dissociation assay decreased fragmentation of primary keratinocytes induced by a monoclonal antibody against Dsg3, and by PV-IgG from two other patients both suffering from mucosal PV. However, such protective effect was not observed in both cultured cells and ex vivo disease models, when another mucocutaneous PV4-IgG containing more Dsg1 autoantibodies, was used. Taken together, ADAM10 modulates both hyperadhesion and PV-IgG-induced loss of cell adhesion dependent on the autoantibody profile.